Pengaruh Kualitas Kredit dan Modal Inti terhadap Kinerja Keuangan dengan Kebijakan Countercyclical sebagai Variabel Intervening - Mendra (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to find the effect of job stress on job satisfaction, the effect of compensation on job satisfaction, the effect of the work environment on job satisfaction, the effect of job stress on performance, the effect of compensation on performance, the effect of work environment on performance, the effect of job satisfaction on performance, the effect of job stress on teacher performance with job satisfaction as an intervening variable, the effect of compensation on teacher performance with job satisfaction as an intervening variable, the effect of work environment on teacher performance with job satisfaction as an Intervening variable in Chemical Analyst Vocational School Padang. Research conducted in Padang Vocational High Schools , the research population is a teacher of Chemical Analyst Vocational School Padang with 51 civil servants . The sampling technique, the saturated sample, the technique of withdrawing all members of the population are used as samples. The sample is 51 people. Primary data were collected through a questionnaire using a Likert scale model that had been tested for validity and reliability. The data analysis technique used is the Structural Equation Modeling (SEM) analysis tool using the partial least squares (PLS) program. The results of the study are there is an effect of job stress on job satisfaction, there is no effect of compensation on job satisfaction, there is no influence of the work environment on job satisfaction, there is an effect of job stress on performance, there is no effect of compensation. on performance, there is no effect of work environment on performance, there is no effect of job satisfaction on performance, there is no effect of work stress on teacher performance with job satisfaction as an intervening variable, there is no effect of compensation on teacher performance with job satisfaction as an intervening variable, the effect of the work environment on teacher performance with job satisfaction as an intervening variable in Chemical Analyst Vocational School Padang